Solid-State NMR (31)P Paramagnetic Relaxation Enhancement Membrane Protein Immersion Depth Measurements - Maltsev, Sergey (American Chemical Society, 2014)
[Image: see text] Paramagnetic relaxation enhancement (PRE) is a widely used approach for measuring long-range distance constraints in biomolecular solution NMR spectroscopy. In this paper, we show that (31)P PRE solid-state NMR spectroscopy can be utilized to determine the immersion depth of spin-labeled membrane peptides and proteins. Changes in the (31)P NMR PRE times coupled with modeling studies can be used to describe the spin-label position/amino acid within the lipid bilayer and the corresponding helical tilt. This method provides valuable insight on protein–lipid interactions and membrane protein structural topology. Solid-state (31)P NMR data on the 23 amino acid α-helical nicotinic acetylcholine receptor nAChR M2δ transmembrane domain model peptide followed predicted behavior of (31)P PRE rates of the phospholipid headgroup as the spin-label moves from the membrane surface toward the center of the membrane. Residue 11 showed the smallest changes in (31)P PRE (center of the membrane), while residue 22 shows the largest (31)P PRE change (near the membrane surface), when compared to the diamagnetic control M2δ sample. This PRE SS-NMR technique can be used as a molecular ruler to measure membrane immersion depth.